2011
DOI: 10.1016/j.ejpain.2010.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain imaging of trigeminal neuralgia

Abstract: We used functional magnetic resonance imaging (fMRI) to analyze changes in brain activity associated with stimulation of the cutaneous trigger zone in patients with classic trigeminal neuralgia (CTN). Fifteen consecutive patients with CTN in the second or third division of the nerve, were included in this study. The fMRI paradigm consisted of light tactile stimuli of the trigger zone and the homologous contralateral area. Stimulation of the affected side induced pain in seven patients, but was not painful in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 51 publications
(93 reference statements)
4
65
0
Order By: Relevance
“…Patients in a crisis should be kept calm because they can feel overwhelmed by the pain and its continuation, which can induce more attacks. 65 For personal use only: See rights and reprints http://www.bmj.com/permissions Subscribe: http://www.bmj.com/subscribe…”
Section: What Are the Surgical Options?mentioning
confidence: 99%
“…Patients in a crisis should be kept calm because they can feel overwhelmed by the pain and its continuation, which can induce more attacks. 65 For personal use only: See rights and reprints http://www.bmj.com/permissions Subscribe: http://www.bmj.com/subscribe…”
Section: What Are the Surgical Options?mentioning
confidence: 99%
“…Additionally, a functional brain imaging study in TN further indicated sensitization of the trigeminal system. 22 …”
Section: General Hyperalgesia Indicative Of Central Sensitizationmentioning
confidence: 99%
“…Studies with deep brain stimulation of the hypothalamus give further evidence of the role of the hypothalamus in SUNCT [56]. Functional brain imaging of TN in 15 patients with second or third division trigeminal involvement showed increased activity in the spinal trigeminal nucleus, thalamus, primary and secondary somatosensory cortices, anterior cingulate cortex, insula, premotor/motor cortex, prefrontal areas, putamen, hippocampus and brainstem [57]. To date, functional neuroimaging studies in first division TN have not been completed.…”
Section: Brain Activation Patterns On Functional Imagingmentioning
confidence: 99%